Historical Approach and Analysis of Roles and Functions of Indonesian Mosques - Tandos, Rosita (Asian Social Work Journal, 2024)
Several studies show how mosques become a symbol of Islam, entities of Muslims and civilizations, and play important roles in society. Using historical approach and social welfare perspectives, the study aims to explore roles and functions of mosques in two periods of early Islam and modern era. The last provides description of mosques in some Muslim and non-Muslim countries such as in Indonesia, Turkey, Morocco and United States. The study also shows the need for revitalizing the role of mosques by applying short survey, in-depth interview and secondary data in collecting, analysis and explain solutions in the eyes of congregations of some Indonesia mosques in improving programs, activities and services particularly for special needs such as interfaith, youth and women groups.